2013
DOI: 10.1371/journal.pone.0072333
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphism of 9p21.3 Locus Is Associated with 5-Year Survival in High-Risk Patients with Myocardial Infarction

Abstract: ObjectiveThe rs1333049, rs10757278 and rs4977574 are single nucleotide polymorphisms (SNPs) of chromosome 9p21 locus that are associated with prevalence of acute coronary syndromes (ACS). The rs1333049 SNP was also associated with cardiac outcome 6 months post ACS. No data concerning their association with long term prognosis after myocardial infarction is available. The aim of our study was to investigate the association of the 9p21.3 locus with 5-year overall mortality in patients with ST-elevation myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…This phenomenon is probably related to an increased number of events in the chosen subgroup and was observed neither in medium-risk, nor in low-risk patients. Surprisingly, the genotype associated with increased risk for myocardial infarction showed a protective effect in terms of further prognosis, instead of deteriorating it, as reported in some studies as well as in the previous retracted version of this article [28]. Our new findings are additionally confirmed by results from the validation group.…”
Section: Discussionsupporting
confidence: 85%
“…This phenomenon is probably related to an increased number of events in the chosen subgroup and was observed neither in medium-risk, nor in low-risk patients. Surprisingly, the genotype associated with increased risk for myocardial infarction showed a protective effect in terms of further prognosis, instead of deteriorating it, as reported in some studies as well as in the previous retracted version of this article [28]. Our new findings are additionally confirmed by results from the validation group.…”
Section: Discussionsupporting
confidence: 85%
“…Among cardiovascular events, ischemic strokes showed the strongest association with ANRIL SNP rs10757278 in comparison with myocardial events. These results are supported by the univariate model for Cox regression where homozygous patients GG for ANRIL SNP rs10757278 showed a higher risk of a cardiovascular event occurring than AA or AG patients, confirming the findings of studies focusing on the general population . Moreover, the hazard ratio was higher (HR = 4.09) when only ischemic stroke was considered compared with both multiple event types (HR = 2.65).…”
Section: Discussionsupporting
confidence: 82%
“…Significant associations have been revealed between the risk 9p21.3 genotypes and the outcomes in the most severe cases of MI with multi-vessel coronary artery burden or high risk according to the GRACE score (15,16). The results of the present study indicated that future clinical application of genomic data requires accurate definition of the target group of patients.…”
Section: Clinical Application Of Chromosome 9p213 Genotyping In Patimentioning
confidence: 58%